To solve the equation, we need to first simplify the equation on both sides.
9/2 = x + 4/6
To simplify the equation, we can find a common denominator for the fractions on the right side of the equation. The common denominator for 2 and 6 is 6.
Converting 9/2 to an equivalent fraction with a denominator of 6 gives us:
9/2 = 9 * 3 / 2 * 3 = 27/6
Thus, the equation becomes:
27/6 = x + 4/6
Now, we can subtract 4/6 from both sides of the equation to isolate x:
27/6 - 4/6 = x + 4/6 - 4/6
(27-4)/6 = x + 0
23/6 = x
Therefore, the solution to the equation is:
x = 23/6
9/2 = x + 4/6
1 answer